Public Interest Litigation (PIL) and Environmental Constitutionalism: Exploring the Nexus of Judicial Activism and Environmental Protection in India (Maharaja Surajmal Institute Law Journal, 2025)
In recent decades, the concept of Public Interest Litigation (PIL) has emerged as a potent instrument within the paradigm of environmental constitutionalism in India. This research paper aims to examine the intricate relationship between PIL and environmental constitutionalism, shedding light on how PIL has contributed to the advancement of environmental protection and sustainability objectives in the legal system of India. The paper begins by contextualizing the concept of environmental constitutional ism within the Indian legal landscape, emphasizing the integration of environmen tal principles into the constitutional framework through articles such as Article 211 and Article 48A2. It explores the inherent tensions between environmental rights and developmental imperatives, setting the stage for the subsequent analysis of PIL’s role in reconciling these tensions. A comprehensive review of landmark environmental PIL cases is conducted to illus trate the extent to which judicial activism has shaped environmental jurisprudence. The paper examines cases that have brought about significant policy changes, influ enced regulatory frameworks, and compelled governmental action to prevent and remedy environmental harm. Through this analysis, the paper highlights the trans formation of PIL from a mere procedural tool to a mechanism for enforcing environ mental rights and holding authorities accountable for their constitutional obligations. Furthermore, the paper delves into the implications of PIL for access to justice, emphasizing its role in democratizing the legal process by providing marginalized communities and environmental activists with a platform to advocate for their rights.
Keywords: Public Interest Litigation (PIL); Environmen- tal Constitutionalism; Judicial Activism; Environmental Protection